2020
DOI: 10.1080/14737175.2020.1826930
|View full text |Cite
|
Sign up to set email alerts
|

From QAAPAPLE 1 to QAAPAPLE 2: how do we move from one algorithm to another one with Long Acting Antipsychotics (LAIs)

Abstract: Background: In 2011, the authors published an algorithm summarizing practice guidelines related to the use of long-acting antipsychotics (LAIs) called the Québec Algorithme Antipsychotique à Action Prolongée (QAAPAPLE), and proposed that it be revised every 5-10 years to update it according to most recent scientific knowledge. Therefore, a re-evaluation of the algorithm was conducted to determine which recommendations were still relevant and which needed modification. Methods: The authors conducted a twofold a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…43 The lack of specific recommendations regarding injectable APs in practice guidelines may explain that few patients of the study cohort initiated or reinitiated a LAI SGA. Even though clinical guidelines do not state clearly what should be the pharmacological AP treatment to initiate for patients with schizophrenia, 15,[34][35][36][44][45][46][47] our findings reinforce the idea that initiating or reinitiating LAI SGAs may have benefits for patients with schizophrenia.…”
Section: Long-acting Injectable Secondgeneration Antipsychoticsmentioning
confidence: 56%
“…43 The lack of specific recommendations regarding injectable APs in practice guidelines may explain that few patients of the study cohort initiated or reinitiated a LAI SGA. Even though clinical guidelines do not state clearly what should be the pharmacological AP treatment to initiate for patients with schizophrenia, 15,[34][35][36][44][45][46][47] our findings reinforce the idea that initiating or reinitiating LAI SGAs may have benefits for patients with schizophrenia.…”
Section: Long-acting Injectable Secondgeneration Antipsychoticsmentioning
confidence: 56%
“…Improvements in terms of symptom severity, illness severity, response and remission appeared more pronounced in younger patients up to 35 years compared with the patients older than 35 years, suggesting that young patients may particularly benefit from AOM treatment. The argument has been raised that LAI antipsychotics should be offered early in the course of the disease [15,22,23], which is also reflected in the treatment guideline of Québec [8] as well as a consensus statement from the Taiwanese Society of Biological Psychiatry and Neuropsychopharmacology [24].…”
Section: Discussionmentioning
confidence: 99%
“…One way to improve adherence is the use of long-acting injectable antipsychotics (LAI) that offer reliable medication delivery and stable pharmacokinetics and also facilitate monitoring of non-adherence, thereby decreasing e. g. the risk of misuse, of unnecessary medication changes, or of evaluating an insufficient treatment response as "therapy refractive" [7]. There is growing evidence that LAIs should not be seen as a last resort, but rather used in the early phase of the disorder to prevent relapse and hospitalization, as recommended for instance in Québec's guidelines [8]. In the most recent and comprehensive meta-analysis studying the effectiveness of LAIs across different study designs, LAIs were more effective in preventing hospitalization or relapse in settings ranging from restricted research (randomized controlled trials -RCTs) to real-word application (cohort and pre-post studies) [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, new oral and new long‐acting injectable (LAI) antipsychotics have been introduced into the treatment options 8 . LAI antipsychotics have demonstrated their place as first‐line treatment for schizophrenia at various stages of the disease 9–16 17,18 reducing time to first hospitalization and readmission rates 14 …”
Section: Introductionmentioning
confidence: 99%
“…8 LAI antipsychotics have demonstrated their place as first-line treatment for schizophrenia at various stages of the disease. [9][10][11][12][13][14][15][16] Their efficacy has been established over oral agents, 17,18 reducing time to first hospitalization and readmission rates. 14 Kane et al (2020) 14 demonstrated the usefulness of LAI SGAs in early disease progression in a multicenter RCT.…”
Section: Introductionmentioning
confidence: 99%